Recent developments in psychosocial interventions for people with psychosis - McCann, Edward (My University, 2001)
The advent of drug treatments for psychotic illness in the 1950s, along with changes in social policy, heralded the move from institutionalized care to community care. Over the last decade, there have been research developments in the use of psychological techniques to manage psychotic symptomatology, particularly in the realms of cognitive behavioral therapies. There is growing evidence to suggest that psychological treatments can offer an adjunct or even an alternative to traditional medical treatments for patients with schizophrenia and other serious mental illnesses. Opportunities have arisen for mental health nurses to learn these new approaches to caring for people with enduring mental illnesses. The impact of psychological interventions in the treatment of psychosis and the implications for mental health nursing practice are discussed.
PUBLISHED
Keywords: psychosocial interventions; family work; family interventions; psychosis; CBT; schizophrenia; family therapy; psychotherapy